An oropharyngeal pH monitoring device to evaluate patients with chronic laryngitis. Issue 5 (18th March 2013) - Yuksel, E. S.; Slaughter, J. C.; Mukhtar, N.; Ochieng, M.; Sun, G.; Goutte, M.; Muddana, S.; Gaelyn Garrett, C.; Vaezi, M. F.
Abstract Background Diagnostics for gastro‐esophageal reflux disease (GERD) are suboptimal because of limited sensitivity. We performed in vitro and in vivo studies to systematically assess the performance characteristics of an oropharyngeal pH probe. Methods In vitro studies compared the oropharyngeal probe with a standard pH catheter in liquid and aerosolized solutions, pH 1–7. The accuracy of measurements, deviation from target pH, and time to equilibrium pH were determined. Simultaneous distal esophageal pH measurements were obtained in 11 patients with GERD. Oropharyngeal and distal esophageal reflux parameters were measured for controls (n = 20), patients with GERD (n = 17), and patients with chronic laryngitis (n = 10). Key Results In the liquid phase, at pH 4–5, the oropharyngeal probe had less deviation from the target value than the standard catheter; deviation in the vapor phase was similar (0.4 pH units). Median (interquartile) time to reach equilibrium pH was significantly (P < 0.001) faster with the oropharyngeal than the standard probe. In comparing simultaneous distal esophageal pH characteristics, 96% of recordings with the new and standard probes were in agreement to within ±1.0 pH unit; 71% of recordings were in agreement within ±0.5 pH units. Patients with chronic laryngitis had significantly higher levels of oropharyngeal acid exposure at pH <4, <5, and <6, in the upright position than patients with GERD or controls (P < .001). Conclusions & Inferences Oropharyngeal pH monitoring appears to be more sensitive than traditional pH monitoring in evaluation of patients with extraesophageal reflux. It is a promising tool in evaluation of this difficult group of patients.